PENGARUH MOTIVASI EKONOMI, MOTIVASI KARIR, PENGETAHUAN PERPAJAKAN, DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA AKUNTANSI BERKARIR DI BIDANG PERPAJAKAN (Studi Empiris Mahasiswa Jurusan Akuntansi Universitas Riau, Universitas Andalas, Universitas Padjadjaran, dan Universitas Gadjah Mada) - Rahmawan Azzaky Muhammad; Zirman Zirman; Azhar A Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to find out about the effect of economic motivation, career motivation, taxation knowledge, and job market considerations on accounting students' interest in taxation career. In this study, data analysis is using descriptive statistics, while the population and sample were students majoring in accounting Class of 2017 at Universitas Riau, Universitas Andalas, Universitas Padjadjaran, and Universitas Gadjah Mada. Hypothesis testing in this study is using the T-test which aims to determine whether there is an influence between independent variable and dependent variable individually for each variable. The statistical test tools used are SPSS For Windows and Microsoft Excel 2019, while research data is obtained from questionnaires distributed to respondents using an online-based Google Form. The results of the study indicate that economic motivation, career motivation, and taxation knowledge affect the accounting students’ interest in taxation career, while job market considerations do not affect the interest of accounting students in a career in taxation.Keywords : Economic motivation, career motivation, taxation knowledge, job market considerations, accounting students’ interest in taxation career